2000
DOI: 10.1111/j.1572-0241.2000.01943.x
|View full text |Cite
|
Sign up to set email alerts
|

Segmental colitis associated with diverticula: a prospective study

Abstract: This endoscopic picture is not an exceptional finding. Hematochezia was the main clinical feature, and no relation with gender, age, or smoking habit was found. Blood chemistries were generally normal and the rectum was spared. The histological features were not diagnostic and most patients did not complain of any abdominal symptoms 12 months after enrollment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 7 publications
4
48
0
3
Order By: Relevance
“…7 This pattern was termed diverticular colitis, 8 crescentic fold disease, 9 diverticular disease-associated colitis, 10,11 isolated sigmoiditis, and segmental colitis associated with diverticulosis. [12][13][14] However, this terminology applies only to patients with diverticulitis without an established diagnosis of IBD, while only a small minority of these patients will progress to classic IBD. 10,15,16 Two studies approached the question of a possible mutual interaction between IBD and diverticulosis on the development and nature of inflammation; Meyers et al 17 suggested that CD in the setting of diverticulosis may lead to development of diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…7 This pattern was termed diverticular colitis, 8 crescentic fold disease, 9 diverticular disease-associated colitis, 10,11 isolated sigmoiditis, and segmental colitis associated with diverticulosis. [12][13][14] However, this terminology applies only to patients with diverticulitis without an established diagnosis of IBD, while only a small minority of these patients will progress to classic IBD. 10,15,16 Two studies approached the question of a possible mutual interaction between IBD and diverticulosis on the development and nature of inflammation; Meyers et al 17 suggested that CD in the setting of diverticulosis may lead to development of diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Imperiali et al found retrospective prevalence of 0.36% of SCAD in a total of 5,457 patients recorded in five Italian endoscopic centers, with prevalence falling afterwards to 0.25% as six patients were soon discharged to other diagnosis [7]. Endoscopic prevalence was therefore 1.15% of patients with diverticulosis, with mean age of 66.5 years [7].…”
Section: Epidemiologymentioning
confidence: 97%
“…In addition to other pelvic disease and to infectious or inflammatory bowel disease, special forms of inflammatory or otherwise abnormal mucosa coexisting with diverticulosis must be considered, in order to avoid a too liberal ‘definition’ of diverticulitis, e.g. NSAID colitis, ischemia [7], diverticular colitis [8,9,10,11,12], mesenteric inflammatory veno-occlusive disease [13], coexistence of Crohn’s disease and diverticulosis or diverticulitis [14,15,16,17], and prolapsing mucosal folds in diverticular disease [18,19]. Not taking care for these differentiations makes it very difficult to compare patients, rationales and results from the literature.…”
Section: What Is Recurrent Diverticulitis?mentioning
confidence: 99%